TÜRKİYE’DE UYGULANMAKTA OLAN HEKİM MESLEKİ SORUMLULUK SİGORTALARINA YÖNELİK BİR ARAŞTIRMA - AKPINAR, ÖZGÜR (My University, 2018)
Ülkemizde sorumluluk sigortaları branşında ağırlıklı üretim kara araçlarına bağlı sorumluluk sigortalarındadır. Kanun koyucu toplumun ihtiyaçlarını da göz önünde bulundurarak çeşitli alanlarda zorunlu sorumluluk sigortası uygulamalarını başlatmıştır. Bu durum sorumluluk sigortaları alanında ürün çeşitliliğinin artmasını sağlamıştır. Hekim mesleki sorumluluk sigortaları da bu kapsamdaki sigorta türlerinden biridir. Dünyada tarihi eskiye dayanan hekim mesleki sorumluluk sigortaları, ülkemizde 2010 yılında zorunlu tutulmaya başlamıştır. Yıllar içinde teminat tutarlarında değişiklik olsa da primlerde değişiklik yapılmamıştır. Biriken dava sayıları ve tazminat tutarları ile başlarda kar etmekte olan bu sigorta ürünü, zarar eder hale gelmiştir. Çalışmamızda zorunlu hekim mesleki sorumluluk sigortalarının geldiği son durum incelenmek istenmiştir. Ülkemizdeki uygulamaları, zorunlu tutulan poliçe ile ilgili üretim ve hasar verileri incelenmiştir. Saha çalışması yapılarak, hekimlerin görüşleri alınmış, sigorta ve sorumluluk bilinçleri tespit edilmeye çalışılmıştır. Çalıştıkları kurum, mesleki deneyim süreleri ve uzmanlıklarına göre sigorta yaklaşımları ölçülmüştür. Analizler, hekimlerin mesleki sorumluluk sigortasının gerekliliğine inandıklarını, daha çok bilgi sahibi olmaları gerektiğini ve bu sigorta ürününün gelişmesine ihtiyaç duyduklarını göstermiştir. Görüşlerinin olumlu olduğunu bir miktar şüphe duysalar da sigortanın varlığının kendilerini rahatlattığını beyan etmişlerdir. Bu sigorta türünün yaşayabilmesi için uygun prim ve teminat içeriğine sahip olması gerekmektedir. Hekimler sigorta içeriği hakkında bilgilendirilmeli, dava süreçlerinde hekimler kanuni yetkililer, meslek odaları ve sigorta şirketleri ortak çalışmalıdır.

It is expected that people will assume the consequences of their defective behaviors in their responsibilities. Also, the legal systems require the compensation for damages of faulty owners. This is the scope of liability insurances. Considering the needs of society, the regulatory can implement compulsory liability insurance in various fields. Liability insurances and medical malpractice insurance are also included in this scope. Professional liability insurance provides coverages for damages that the insured can give to the third person while applying his profession. Medical Malpractice Insurance provides financial coverage for physicians against damages they may give to their patients while they are practicing their profession. Physicians are responsible for medical malpractice other than the standard medical treatments that physician is responsible for. Medical malpractice is defined as the failure of the physician to perform standard practice during treatment, the lack of skills or the loss of treatment to the patient. It is different from the situations seen during medical practice and the conditions of the physician (complication). The complication is that the adverse event which is the result of the medical intervention is not protected or prevented by known methods. Medical malpractice can be examined in three groups; diagnosis, treatment and other application errors. Before the treatment begins, the physician should examine the findings of the patient and diagnose correctly. It should be able to choose the appropriate method of diagnosis and provide the correct application through medical knowledge, skill and cure. Failure to follow the patient in the post-treatment period, incorrect dose adjustment in the drug applications, wrong or incomplete implementation of the preventive and protective applications and not keeping the patient records are considered as medical malpractice. The medical malpractice insurance of physicians based on historical documents in the world started to be compulsorily enforced in our country on 21 July 2010 by the communiqué published in the Official Gazette No. 27648. “Compulsory Financial Liability Insurance for Medical Malpractice” was established by the regulatory. These compulsory policy coverages are both claims made and occurence basis. Although there has been some changes in the amount of coverage over the years, the premium has not been amended. For this reason, this insurance product, which is profitable at the beginning, with the accumulated number of lawsuits and compensation amounts has made loss. Direct premium production of Compulsory Financial Liability Insurance for Medical Malpractice was 48,267,453,08 TL in 2016 and the loss / premium ratio reached to198,07%. According to the Medical Liability Insurance Tariff and Instructions, the per capita and annual coverage limits vary between 200,000-TL and 800,000-TL according to 4 different risk groups. In all cases the annual limit is limited to 1,800,000 TL. It includes both material and non-pecuniary compensation claims and costs of proceedings. Even if the risk is realized within the policy period, the amount of the anuual coverage limit remains the same during the contract period. Medical malpractice insurance has different applications in the world. The most useful application is considered to be a no-fault system being applied in the Nordic countries (i.e. Finland, Norway, Denmark etc.). In this system, medical faults are done to detect and remove the causes. The grievance of the patient is covered by the public or private insurance system. The system that is being implemented in our country is a system for the consequences of medical application errors. The medical malpractice case is examined by experts and connected to a conclusion. If it is decided that a physician is faulty, the physician will be liable to pay compensation and will be liable to professional liability insurance. These processes can destroy physicians and patients. It can be thought that a system that takes the precautions before the error has taken place is more constructive, which removes the causes of the mistakes. In our study, it’s desired to examine the latest situation of compulsory medical malpractice liability insurance in our country. The premium production and damage data related to the compulsory policy have been examined. An interview has been applied to pyhsicians, the opinions of the physicians about the insurance and responsibility were taken consciousnesses were tried to be determined. Insurance approaches have been measured according to the institution, professional experience and expertise they have worked for. Analyzes show that physicians believe that professional liability insurance is necessary, they need to have more information, and that this insurance product needs to be developed. Although they have lit
A STUDY OF MEDICAL MALPRACTICE INSURANCE IN TURKEY